Evaluation of bread wheat genotypes under rain-fed conditions in Terai districts of Nepal - Pandey, Deepak; Pant, Khem Raj; Bastola, Biswas Raj; Giri, Rabin; Bohara, Suman; Shrestha, Shankar; Hamal, Govinda Bahadur; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Thirty four percent of the total wheat cultivated area is under rain-fed condition in Nepal and that of the Terai is nineteen percent. The objective of this study was to develop drought tolerant and high yielding varieties of wheat for timely sown rain-fed environments. Coordinated Varietal trial (CVT) was carried out in normal wheat growing season during 2016/17 and 2017/18. The research was conducted at five locations (Rampur, Bhairahawa, Doti, Jitpur and Nepalgunj) of five research stations of Nepal Agricultural Research Council (NARC) throughout the Terai region in alpha lattice design with two replications. Data on different yield attributing traits were recorded. In the CVT-TTL 2016/17 highly significant difference (p<0.01) among the genotypes was found for days to heading, days to maturity, plant height, number of grains per spike and thousand kernel weight and significant difference (p<0.05) for grain yield. The highest grain yield was observed in NL 1326 (2954 kg/ha) which was followed by NL 1327 (2819 kg/ha), NL 1211 (2719 kg/ha), NL1202 (2683 kg/ha), BL 4707 (2654 kg/ha) and BL 4708 (2652 kg/ha). Similarly, in CVT-TTL 2017/18, highly significant difference (p<0.01) among the genotypes was observed for the days to heading, days to maturity and plant height and non-significant different for number of grains per spike, grain yield and TGW. However, Genotype by Environment (G x E) was found highly significant (p<0.01) for the days to heading, plant height, grain yield and TGW and significant different (p<0.05) for number of grains per spike. The highest grain yield was obtained in NL1322 (2305 kg/ha) which was followed by NL1369 (2287 kg/ha), NL 1202 (2205 kg/ha), BL 4708 (2197 kg/ha) and BL 4820 (2118 kg/ha). Among these tested genotypes BL 4708, NL 1202, NL 1211, NL 1307, NL 1327 and NL 1369 are recommended for the coordinated farmer’s field trial for further verification and release as variety.